Hybrid Retrieval Reduces Hallucinations in Mistral-7B Across Legal and Scientific Domains - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 16 peer-reviewed papers addressing the following research question: How does the hybrid retrieval approach perform in mitigating hallucinations in Mistral-7B when applied to domain-specific benchmarks beyond religious texts, such as legal or scientific corpora,. 10 claims were extracted from source literature; 0 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 4.0/10. This report is a
Machine-generated literature synthesis.